Prevalence and Factors Associated to Household Food Insecurity During COVID-19 Outbreak (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2021)
COVID-19 outbreak added unprecedented threatens to the food system worldwide. The enactment of social restriction regulation by several provinces in Indonesia may give an impact to household food security. Economical access to food might be compromised since the application of work from home policy, particularly for those who earn income from informal sector jobs. This study aims to determine the proportion of household food insecurity during the COVID-19 pandemic, identify the associated factors, and the strongest predictor of household food insecurity. This cross-sectional study design was carried out in Java and Sulawesi. A Self-administered Google Form Questionnaire was filled out by 191 women of reproductive age as the household food gatekeeper. Household food insecurity was evaluated using the Food Insecurity Experience Scale (FIES) Questionnaire by FAO that consisted of eight gradual questions. Data analysis was performed using statistical software for univariate, bivariate (chi-square), and multivariate (logistic regression). The proportion of food insecurity in the study was 29.8%, encompassed 19.9% mild food insecure, 7.3% moderate food insecure, and 2.6% severe food insecure. Food insecurity was significantly associated with place of residence, family income, and education. Living in urban areas was among the robust predictor of household food insecurity (OR 5.59, CI 95%), meaning living in urban was a risk factor of household food insecurity during the COVID-19 pandemic. Urban living was highly dependent on routine salary since they might not occupy with some sort of alternative source for income like in the rural areas, however, there was income reduction during the crisis. Food insecurity might be a sting in the tail of the COVID-19 pandemic, food policy regarding this matter is urgently required.